Hemp-Derived CBD Used in Food and Food Supplements - Bartončíková, Michaela; Lapčíková, Barbora; Lapčík, Lubomír; Valenta, Tomáš (Molecules (Basel, Switzerland), 2023)
Cannabis sativa L., a plant historically utilized for textile fibers, oil, and animal feed, is progressively being recognized as a potential food source. This review elucidates the nutritional and functional attributes of hemp and cannabidiol (CBD) within the context of food science. Hemp is characterized by the presence of approximately 545 secondary metabolites, among which around 144 are bioactive cannabinoids of primary importance. The study looks in detail at the nutritional components of cannabis and the potential health benefits of CBD, encompassing anti-inflammatory, anxiolytic, and antipsychotic effects. The review deals with the legislation and potential applications of hemp in the food industry and with the future directions of cannabis applications as well. The paper emphasizes the need for more scientific investigation to validate the safety and efficacy of hemp components in food products, as current research suggests that CBD may have great benefits for a wide range of consumers.
Keywords: food products; potravní doplňky; Cannabinoids; Cannabidiol; kanabidiol; Hallucinogens; Dietary Supplements; health benefits; halucinogeny; CBD; cannabinoids; kanabinoidy; Cannabis; Animals; functional properties; hemp; nutrition; zvířata